Gastric Perforation Due to Blunt Trauma Abdomen - Rattan, Kamal Nain; Agarwal, Mansi; Bansal, Shruti; Gurupriya, J (Journal of Nepal Paediatric Society, 2018)
Blunt trauma abdomen rarely leads to gastrointestinal injury in children and isolated gastric rupture is even rarer presentation. We are reporting a case of isolated gastric rupture after fall from height in a three year old male child.